Notes - Dirk Vanderbeke, John M. Krafft, Khachig Tölölyan, Bernard Duyfhuizen (Pynchon Notes, 1998)
The final presentation at the Antwerp conference during International Pynchon Week in June 1998 was The Narrated Gravity's Rainbow–a critical reading/performance of Pynchon's novel by Project Vox Libris. Their reading of the novel centers on the ideas of Europe as a Zone of conflicting human and technological forces, the transformation of power in the ever-changing shapes of entertainment, and the evolution of technology from V-2 missiles to space dreams and computer mirages. Spanning several orthodox categories, The Narrated Gravity's Rainbow integrates criticism with animated digital collage (using the work of Canadian artist Larry Daw), theatre and contemporary music into a compelling aural and visual performance, transforming Pynchon's postmodern fiction into Performance Art. The entire presentation is now available on CD-ROM or PAL-format VHS video for 12.00 (U.S.) plus postage. An order form is available on the Pynchon Notes website at <http://www.ham.muohio.edu/ krafftjm/voxLibris.html>.